Convenor - Manganaris, George A. (My University, 2026)
The X ISHS Peach Conference was assigned to be held in Naoussa, Greece, as a joint initiative of CUT and Aristotle University of Thessaloniki during 1-4 June 2021. Currently, the website of the Symposium provides information regarding: preliminary scientific program, scientific committee, registration packages. The website with all relevant information is www.fruitsciences.eu/peach2021